The influence of political hegemony on the emergence of Shiite jurisprudence and the reasons for the delay of its writing during the first Abbasid period (132-247 AH/750-861 AD) - Goran Abdullah Hama-Ali Dasni; Dr.Kaiwan Aazad Anwar (Journal of College of Education, 2025)
The Influence of political Dominance on the Emergence of Shiite Jurisprudence and the Reasons for its late development in the Early Abbasid Period (132-247 AH/750-861 AD) Jurisprudence is the basis of Islamic Shari'ah and its completion through which religious scholars and Islamic thinkers could interpret and clarify Shari'ah texts and understand them in accordance with texts of the Qur'an, the sayings of Prophet (peace and blessings of Allaah be upon him), the sayings attributed to the Companions, and personal opinion of Muslim scholars and their fatwas. These scholarly contributions came as responses to the queries, problems, and misunderstandings faced by the Muslim community. During the early Abbasid period, Shi‘a jurists faced a prolonged period of political restriction, which restricted their ability to freely disseminate and improve their juristic stances and theoretical basis.This study aims to highlight the political influence during that period on the emergence and development of Shi‘a jurisprudence, as well as to clarify the reasons behind the delay in its compilation until the early Abbasid era. To maintain this aim, the study adopts a comparative historical-analytical methodology, tracing the political circumstances that shaped Shi‘a legal thought and analyzing the factors that contributed to the delay in its documentation. We have divided the content of the research into six different sections that include the objectives of the research The study ends with the main key findings and recommendations.
Keywords: Jurisprudence; Imamate; Personal opinion; Shi‘a; Politics